Phenotypic plasticity of male calls in two populations of the katydid Neoconocephalus triops (Insecta: Tettigoniidae) - Beckers, Oliver M.; Kijimoto, Teiya; Schul, Johannes (Frontiers in Ecology and Evolution, 2023)
The ability to respond to environmental changes plays a crucial role for coping with environmental stressors related to climate change. Substantial changes in environmental conditions can overcome developmental homeostasis, exposing cryptic genetic variation. The katydid Neoconocephalus triops is a tropical species that extended its range to the more seasonal environment of North America where it has two reproductive generations per year. The harsher winter conditions required adults to diapause which resulted in substantially different mating calls of the diapausing winter animals compared to the non-overwintering summer animals in northern Florida. The summer call corresponds to that of tropical populations, whereas the winter call represents the alternative call phenotype. We quantified call plasticity in a tropical (Puerto Rico) and a temperate population of N. triops (Florida) that differ in experiencing winter conditions in their geographic regions. We hypothesized that the plastic call traits, i.e., doublepulse rate and call structure, are regulated independently. Further, we hypothesized that phenotypic plasticity of double-pulse rate results in quantitative changes, whereas that of call structure in qualitative changes. We varied the photoperiod and duration of diapause during male juvenile and adult development during rearing and analyzed the double-pulse rate and call structure of the animals. Double-pulse rate changed in a quantitative fashion in both populations and significant changes appeared at different developmental points, i.e., the double-pulse rate slowed down during juvenile development in Florida, whereas during adult diapause in Puerto Rico. In the Florida population, both the number of males producing and the proportion of total call time covered by the alternative call structure (= continuous calls) increased with duration spent in diapause. In the Puerto Rico population, expression of the alternative call structure was extremely rare. Our results suggest that the expression of both pulse rate and call structure was quantitative and not categorical. Our systematic variation of environmental variables demonstrated a wide range of phenotypic variation that can be induced during development. Our study highlights the evolutionary potential of hidden genetic variation and phenotypic plasticity when confronted with rapidly changing environments and their potential role in providing variation necessary for communication systems to evolve.